Performance evaluation of 2x2 planar arrays rectangular compared to 2x2 planar array circular microstrip patch antenna / Nik Mohd Amri Nik Azmi - Nik Azmi, Nik Mohd Amri (2010)
This paper discovers the performance evaluation 2x2 planar array rectangular compared to 2x2 planar array circular microstrip patch antenna. In this study, the 2 x 2 planar array rectangular microstrip patch antenna is named as structure 1 and 2x 2 planar array circular microstrip patch antenna is named as structure 2. The study concentrates on frequency of 5.8GHz in reference to the Wimax characteristics. The antennas have been designed use by Flame Retardant 4 (FR-4). It has been simulated using Computer Simulation Technology (CST) Microwave Studio in CST2009 software. Return loss (Sn), Voltage Standing Wave Ratio (VSWR) and Gain (Ghz) values were obtained from simulations of the both antennas and were compared. The best performance for Return loss (Su), Voltage Standing Wave Ratio (VSWR) and Gain (Ghz) out of both antenna types were concluded. Structure 1 antenna gave better results in comparison to the structure 2 antenna, which is reversed from the theory